(untitled) (Applied Biological Research, 2012)
Two year field studies were conducted at Experimental Farm, SKUAST Kashmir to evaluate the effect of 60, 90 and 120 kg N ha-1on fodder maize sown at seeding rate of 40, 60 and 80 kg ha-1. Application of 120 kg N ha-1significantly increased green and dry fodder yields of maize due to increase in all yield components studied viz., plant height, leaf area index, dry matter production and stem diameter. Seed rate of 60 and 80 kg ha-1, being at par, significantly increased plant height and dry matter over 40 kg seed rate ha-1, whereas, leaf area index recorded significantly higher values up to 80 kg seed rate ha-1. Stem diameter recorded significantly lower values with increasing seed rates but green and dry fodder-yield values were realized statistically higher up to 80 and 60 kg seed rate ha-1, respectively. Fodder maize sown at seed rate of 80 kg ha-1and receiving 120 kg N ha-1seems to be the best combination in getting maximum green, succulent and palatable fodder under temperate conditions of Kashmir.